Comparison of the Coracoid, Distal Clavicle, and Scapular Spine for Autograft Augmentation of Glenoid Bone Loss: A Radiologic and Cadaveric Assessment. Issue 3 (March 2022) - Rodriguez, Santiago; Mancini, Michael R.; Kakazu, Rafael; LeVasseur, Matthew R.; Trudeau, Maxwell T.; Cote, Mark P.; Arciero, Robert A.; Denard, Patrick J.; Mazzocca, Augustus D.
Background: Glenohumeral instability caused by bone loss requires adequate bony restoration for successful surgical stabilization. Coracoid transfer has been the gold standard bone graft; however, it has high complication rates. Alternative autologous free bone grafts, which include the distal clavicle and scapular spine, have been suggested. Study Design: Controlled laboratory study. Purpose: The purpose of this study was to determine the percentage of glenoid bone loss (GBL) restored via coracoid, distal clavicle, and scapular spine bone grafts using a patient cohort and a cadaveric evaluation. Methods: Autologous bone graft dimensions from a traditional Latarjet, congruent arc Latarjet, distal clavicle, and scapular spine were measured in a 2-part study using 52 computed tomography (CT) scans and 10 unmatched cadaveric specimens. The amount of GBL restored using each graft was calculated by comparing the graft thickness with the glenoid diameter. Results: Using CT measurements, we found the mean percentage of glenoid restoration for each graft was 49.5% ± 6.7% (traditional Latarjet), 45.1% ± 4.9% (congruent arc Latarjet), 42.2% ± 7.7% (distal clavicle), and 26.2% ± 8.1% (scapular spine). Using cadaveric measurements, we found the mean percentage of glenoid restoration for each graft was 40.2% ± 5.0% (traditional Latarjet), 53.4% ± 4.7% (congruent arc Latarjet), 45.6% ± 8.4% (distal clavicle), and 28.2% ± 7.7% (scapular spine). With 10% GBL, 100% of the coracoid and distal clavicle grafts, as well as 88% of scapular spine grafts, could restore the defect ( P < .001). With 20% GBL, 100% of the coracoid and distal clavicle grafts but only 66% of scapular spine grafts could restore the defect ( P < .001). With 30% GBL, 100% of coracoid grafts, 98% of distal clavicle grafts, and 28% of scapular spine grafts could restore the defect ( P < .001). With 40% GBL, a significant difference was identified ( P = .001), as most coracoid grafts still provided adequate restoration (congruent arc Latarjet, 82.7%; traditional Latarjet, 76.9%), but distal clavicle grafts were markedly reduced, with only 51.9% of grafts maintaining sufficient dimensions. Conclusions: The coracoid and distal clavicle grafts reliably restored up to 30% GBL in nearly all patients. The coracoid was the only graft that could reliably restore up to 40% GBL. Clinical Relevance: With "subcritical" GBL (>13.5%), all autologous bone grafts can be used to adequately restore the bony defect. However, with "critical" GBL (≥20%), only the coracoid and distal clavicle can reliably restore the bony defect.